2012
DOI: 10.1180/claymin.2012.047.3.06
|View full text |Cite
|
Sign up to set email alerts
|

Fe-loaded zeolites as catalysts in the formation of humic substance-like darkcoloured polymers in polycondensation reactions of humic precursors

Abstract: To enhance the catalytic activities of zeolites for the polycondensation reactions of humic precursors, Fe was loaded into a zeolite via an ion-exchange reaction and the resulting product was subjected to calcination at 773 K. Two types iron-loaded zeolites were prepared using one equivalent (Fe-Z-1) and 10-equivalents (Fe-Z-10) of Fe2+ to the cation-exchange capacity of a natural zeolite from Niki town (Hokkaido, Japan). X-ray diffraction (XRD) patterns and X-ray photoelectron spectroscopy (XPS) spectra showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Manganese oxides typically exhibit highly enhancing performance in humification, which can stimulate combination of phenolic carbon to humic-like substances (HLS) [11][12][13][14][15][16]. Moreover, Fe-loaded zeolites as catalysts can also promote humification, and the yield of HLS increases with the addition of Fe into zeolite [17].…”
Section: Introductionmentioning
confidence: 98%
“…Manganese oxides typically exhibit highly enhancing performance in humification, which can stimulate combination of phenolic carbon to humic-like substances (HLS) [11][12][13][14][15][16]. Moreover, Fe-loaded zeolites as catalysts can also promote humification, and the yield of HLS increases with the addition of Fe into zeolite [17].…”
Section: Introductionmentioning
confidence: 98%
“…HAs, apart from natural sources, can also be synthetized through abiotic humification. This process is based on transformations of humic precursors (e.g., amino acids, sugars, and quinones) to HS in the presence of a metallic oxide (e.g., MnO 2 , Fe 2 O 3 , Al 2 O 3 ), which catalyzes and enhances these transformations [ 70 ]. Yang and Hodson [ 71 ] found that SHLA prepared via abiotic humification, using catechol and glycine as humic precursors and an MnO 2 catalyst, was characterized with higher Cu complexation ability than commercial HA (CHA).…”
Section: Novel Was and Their Applicability For Hms Removal From Somentioning
confidence: 99%